Single Laser Shot Photoinduced Phase Transition of Rubidium Manganese Hexacyanoferrate Investigated by X‐ray Diffraction. Issue 27 (17th June 2019) - Azzolina, Giovanni; Collet, Eric; Mariette, Céline; Cammarata, Marco; Trzop, Elzbieta; Sander, Mathias; Levantino, Matteo; Nakagawa, Kosuke; Tokoro, Hiroko; Ohkoshi, Shin‐ichi; Bertoni, Roman
Abstract: Invited for the cover of this issue are the groups of Eric Collet from Université de Rennes 1, France, and Shin‐ichi Ohkoshi from The University of Tokyo, Japan. The cover image shows the application of X‐ray diffraction at the synchrotron to study photoinduced phase transition in charge‐transfer systems. Abstract : Our goal is to reach new ways to control the physical properties of materials … Read more about the story behind the cover in the Cover Profile and about the research itself in the Communication by E. Collet, R. Bertoni et al.